Characterising timing and pattern of relapse following surgery for localised oesophagogastric adenocarcinoma: a retrospective study - Moorcraft, Sing Yu (BMC Cancer, 2016)
BACKGROUND: Oesophagogastric adenocarcinoma (OGA) has a poor prognosis, even for patients with operable disease. However, the optimal surveillance strategy following surgery is unknown. METHODS: We performed a retrospective review of all patients with OGA who had undergone surgery with radical intent at the Royal Marsden between January 2001 and December 2010. RESULTS: Of the 360 patients with OGA who underwent potentially curative surgery, 100/214 patients (47 %) with oesophageal/gastro-oesophageal junction (GOJ) adenocarcinoma and 47/146 patients (32 %) with gastric adenocarcinoma developed recurrent disease. 51, 79 and 92 % of relapses occurred within 1, 2 and 3 years respectively and the majority of patients relapsed at distant sites. Of the patients who relapsed, 67 % (67/100) with oesophageal/GOJ adenocarcinoma and 72 % of patients with gastric cancer (34/47) were symptomatic at the time of relapse. The majority of asymptomatic relapses were first detected by a rise in tumour markers. There was no difference in disease-free survival between asymptomatic and symptomatic patients, but asymptomatic patients were more likely to receive further treatment and had a longer survival beyond relapse. CONCLUSION: The majority of relapses occur within the first 3 years and at distant sites. Monitoring of tumour markers should be considered as part of a surveillance program.